Production of biologically active compounds from plant sterols using bacteria - Nogovitsina, E. M. (Perm Federal Research Centre Journal, 2013)
The paper describes the capabilities of bacteria as effective biocatalysts of the natural sterol transformation process to produce biologically active substances.